2015
DOI: 10.5483/bmbrep.2015.48.6.139
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inhibitor 5 increases metastasis via Erk-mediated MMP expression

Abstract: Apoptosis inhibitor 5 (API5) has recently been identified as a tumor metastasis-regulating gene in cervical cancer cells. However, the precise mechanism of action for API5 is poorly understood. Here, we show that API5 increases the metastatic capacity of cervical cancer cells in vitro and in vivo via up-regulation of MMP-9. Interestingly, API5-mediated metastasis was strongly dependent on the Erk signaling pathway. Conversely, knock-down of API5 via siRNA technology decreased the level of phospho-Erk, the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…AAC-11 (antiapoptosis clone 11), also called Api5 or FIF, is an antiapoptotic protein whose expression prevents apoptosis following growth factor deprivation (1). Many cancer cells exhibit elevated levels of AAC-11, which were found to correlate with poor prognosis in patients with non-small cell lung cancer and cervical cancer and contribute to tumor invasion and metastases (2)(3)(4)(5)(6)(7)(8)(9)(10). Interestingly, AAC-11 appears to be involved in anticancer drugs-induced apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAC-11 (antiapoptosis clone 11), also called Api5 or FIF, is an antiapoptotic protein whose expression prevents apoptosis following growth factor deprivation (1). Many cancer cells exhibit elevated levels of AAC-11, which were found to correlate with poor prognosis in patients with non-small cell lung cancer and cervical cancer and contribute to tumor invasion and metastases (2)(3)(4)(5)(6)(7)(8)(9)(10). Interestingly, AAC-11 appears to be involved in anticancer drugs-induced apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…AAC-11 interacts with several apoptosis-related proteins and this complex-forming ability, probably favored by its elongated 3D structure (14), appears to be essential for AAC-11 to fulfill its antiapoptotic functions (1,9,11,15,16). Therefore, inhibitors of AAC-11 protein-protein interactions could prove to be of clinical benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Api5 was necessary for the migration of the MCF7 cells induced by E2. Recently, a report indicated that Api5 is involved in the metastatic process by increasing MMP expression [ 29 ]. In vivo , xenografted MCF7 cells depleted for Api5 in nude mice were unable to form actively growing tumors compared to the control and displayed significantly a reduced proliferation index.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu's study identified a positive feedback loop between TOPK and ERK2 [ 30 ]. Accumulating evidence indicates that the ERK pathway can promote the migration and invasion of cancer cells and is closely associated with metastasis [ 46 - 49 ]. Our study demonstrates that when TOPK is highly expressed in CTCs, phospho-ERK is also highly expressed (Figure 3B ), and when TOPK is knocked down, the expression of phospho-ERK was also downregulated (Figure 4E ).…”
Section: Discussionmentioning
confidence: 99%